Relapse multifocal osteomyelitis secondary to septicemia: A case study - Amjad Khan; Arshad Khan; Nayyer Naveed Wazir; Naeem Ullah; Omaid Hayat Khan (Archives of Global Professionals, 2017)
Osteomyelitis is an inexorable and debilitating infection of bones. Mostly, it is a stubborn recurrent infection and follows a long aggressive medical and surgical treatment. The present patient (54 year old female) is a case of chronic osteomyelitis with open trauma following septicemia as a result of accident. The patient got an open fracture of proximal right tibia, and surgical intervention along with pharmacological treatment was performed. A couple of days later, it was noted that there was swelling of the patient right leg, and pus discharge was evident. This infection was due to Enterobacter species as identified by laboratory results. Surgery was repeated for a complete debridement of wound. The case is of unusual interest because of its relentless nature, as even after, more than 38 months of treatment, the patient still suffers from the same discomfort of osteomyelitis and pus discharge is frequently being observed. Prolonged use of various antibiotics (ciprofloxacin, penicillin, fusidic acid, and cloxacillin) was found to control pus discharge to some extent controlled by the usage of pus discharge.